2013
DOI: 10.1186/2193-1801-2-436
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of length-weight relationship and condition factor of spotted snakehead Channa punctata (Bloch) under different feeding regimes

Abstract: Comparative study was conducted to observe the efficacy of different feeding regimes on growth of Channa punctata. Six iso- proteinous diets were prepared by using different agro industrial by-products. Maximum weight gain was recorded with diet having 66.75% rice bran, 11.50% mustard cake, 23.0% groundnut cake, 5% molasses, 1.5% vitamin-mineral mixture and 0.5% salt with specific growth rate of 0.408. The experimental fish recorded the value of exponent ‘b’ in the range of 2.7675 to 4.3922. The condition fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 11 publications
7
63
2
4
Order By: Relevance
“…Thus, L. rohita by virtue of possessing an elongated intestine has more area, for absorption, resulting in complete and efficient digestion and assimilation of ingested diet. Condition factor is an indicator of general fish health conditions and the values obtained in the present study of greater than one showed the well-being of fishes selected for the study [21].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, L. rohita by virtue of possessing an elongated intestine has more area, for absorption, resulting in complete and efficient digestion and assimilation of ingested diet. Condition factor is an indicator of general fish health conditions and the values obtained in the present study of greater than one showed the well-being of fishes selected for the study [21].…”
Section: Discussionmentioning
confidence: 99%
“…The K value depicts robustness or suitability of a species in a habitat and primarily reflects the fish's health status, sexual maturity and the degree of feeding (Williams 2000). It is expressed as weight per unit length and a values of above 1 implies a higher weight or fat fish in relation to length (Datta et al 2013). Therefore, K seems relevant for the fisheries managers to predict the performance of the subsector in differing environments.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadosomatic index of Channa limbata The condition factor also reflects changes in food reserves and is, therefore, an indicator of the general fish condition (Datta et al 2013;Islam et al 2013). This study determined that the spawning season of C. limbata was during the rainy season, with development of the testis and eggs peaking in July and August 2014.…”
Section: Condition Factormentioning
confidence: 99%
“…Pauly (1993) studied the length-weight relationships (LWRs) of a fish to predict weight from length measurements made in the yield assessment. In addition, previous research concerning Channidae concluded that the length-weight and length-length relationships of C. diplogramma, C. marulius, C. striata, C. punctatus and C. punctata followed by allometric growth (Ali et al 2013;Datta et al 2013;Kashyap et al 2014). Hannifar et al (2006) investigated length-weight relationships of Channa punctata from Western River in which the study showed no significant difference (p>0.05) in the LWR as a function of sex.…”
Section: Introductionmentioning
confidence: 99%